Nilai Pendidikan Sosial Keberagamaan Islam Dalam Moderasi Beragama Di Indonesia - Rizkiyah, Tahtimatur; Istiani, Nurul (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
The ongoing cases of radicalism and terrorism in the name of religion in Indonesia necessitate the importance of objectifying moderate religious social values. This study aims to identify the values ​​of Islamic religious social education in religious moderation indicators formulated by the Ministry of Religion of the Republic of Indonesia. This research center uses a normative-philosophical approach with analytical theory in the form of a Prophetic Social Science paradigm that was initiated by Kuntowijoyo. The results of the study show that there are social values ​​of Islamic religiosity in the four indicators of religious moderation. First, the transcendence value in tolerance education is in the form of forming social mindsets and attitudes, both in the context of inter-religious and intra-religious life. Second, the value of humanization in national commitment education and accommodative to local culture in the form of forming mindsets and attitudes to maintain nationalism and plural local wisdom. Third, the value of liberation in anti-radicalism education in the form of forming a productive mindset and attitude in realizing a safe and peaceful life. The theoretical implication of this finding shows that there is a meeting point of the paradigmatic basis between the four indicators of religious moderation and the parallel values ​​of Islamic religious social education.